The Engaged Student Ideal in UK Higher Education Policy. Issue 1 (March 2017) - Kelly, Paul; Fair, Nic; Evans, Carol
Abstract The UK Government's Green Paper (BIS in Fulfilling our potential: teaching excellence, social mobility and student choice. BIS, London, 2015), White Paper (BIS in Success as a knowledge economy: teaching excellence, social mobility and student choice. BIS, London, 2016a) and Higher Education and Research Bill (http://www.publications.parliament.uk/pa/bills/cbill/2016-2017/0004/17004.pdf, 2016) appear to be premised on a normative student ideal in UK higher education policy. This ideal student presupposes a transactional model of student engagement, which relies on the accumulation of knowledge capital by a systemic subject. The current government vision forms part of a long-term shift away from the discourse of social democracy since the policies of the 1960s. This shift towards neoliberal political economy is reflected in the legislation to establish the Office for Students, United Kingdom Research and Innovation and the Teaching Excellence Framework (BIS 2015, 2016a; BIS in Teaching excellence framework: technical consultation for year two. BIS, London, 2016b). Rather than adding to the transactional view of student engagement based on the neoliberal student ideal, this article explores the democratic idea of a higher education multitude in which there might be a more nuanced pedagogic and socio-technical understanding of student engagement for further policy developments.